Microwave treatment in waste rubber recycling – recent advances and limitations - K. Formela; A. Hejna; L. Zedler; X. Colom; J. Canavate (eXPRESS Polymer Letters)
Environmentally-friendly microwave heating is increasingly used in polymer chemistry and technology. The selectivity and highly efficiency in the heat transfer present a huge advantage in systems based on recycling, improving their productivity and economic competitiveness. In case of the industrial recycling of waste rubbers, especially end-of-life tires, microwave-induced devulcanization and pyrolysis are nowadays considered as promising approaches. This work aims to report the recent progress in microwave treatments of vulcanized rubbers with different compositions. Special attention is focused on the correlation between microwave processing parameters and devulcanization/pyrolysis efficiency, which have a significant impact on the structure-property relationships of the obtained products. Moreover, the main challenges affecting the future of the industrial application of the microwave technology in rubber recycling are also discussed.